Discrete Element Modeling on Mechanical Behavior of Heterogeneous Rock Containing X-Shaped Fissure under Uniaxial Compression - Ming Chen; Jian Liu; Zhengyong Xie; Jianjun Liu; Xunjian Hu; Bingyang Li; Yue Cen (Geofluids)
Based on the experimental results of an intact rock specimen under uniaxial compression, particle flow code (PFC2D) was adopted to carry out a discrete element modeling (DEM) for the mechanical behavior of heterogeneous rocks containing X-shaped fissures (two intersecting symmetric single fissures) under uniaxial compression. The influences of β (the acute angle between two single fissures) and the direction angle α (the acute angle between the bisector of β and perpendicular to the loading direction) on the strength, deformation, energy, crack propagation, and ultimate failure mode were analyzed in detail. Numerical simulated results showed the following: (1) Due to the X-shaped fissures, not only the peak strength, elastic modulus, crack initiation stress, and damage stress were significantly reduced, and the reduced degree of the peak strength was obviously greater than that of the elastic modulus, but also the brittleness and energy were significantly weakened. (2) The peak strength and elastic modulus generally decreased with the increase of β and increased with the increase of α. Moreover, the change trends of crack initiation stress, damage stress, boundary energy, and total strain energy at the peak stress were consistent with the peak strength. (3) Regardless of the changes of α and β, models all firstly initiated wing cracks at the two tips of the single fissure with a larger inclination angle, and the crack initiation angle decreased with the increase of the inclination angle of the single fissure. (4) The fracture was dominated by tensile microcracks, and no microcracks were generated in a certain range of the X-shaped fissure center. The failure mode was mainly split along the axial direction, and the failure surface started from the tips of the fissure and extended to both ends of models. (5) The uniaxial compressive strength and elastic modulus increased exponentially with the increase of the homogeneity factor. When the homogeneity factor was small, the microcracks were more evenly distributed in the models; when the homogeneity factor was large, the microcracks were mainly concentrated at the tips of the fissure in the models. This study can provide some references for the correct understanding of the mechanical properties of rock masses containing X-shaped fissures.